The Effect of Personality Traits on Generation Z Financial Literacy - Padmodipoero, Faya Daffani Awinatama; Damayanti, Sylviana Maya (Journal of Business and Management, 2020)
Abstract. In the most recent decade, financial literacy has become the main issue, government agencies and financial institutions have gotten financial literacy as one of their primary focuses in the policy aspects. There is an incredible worry that customers tend to lack financial concepts and don't have the apparatuses they have to settle on budgetary choices. Individuals around the globe are confronted with financial decisions on a daily basis. With the evolving information technology landscape, financial information is more abundant than ever before (Killins, 2017). The improvement of financial literacy is required to contribute to a more stable financial system and reduce financial fragility. As a Generation Z that started entering the young adult stage, they faced phenomenal money related and complexity in today's demanding financial environment. As they begin getting older, they should make choices on their own regarding the retirement funds, insurance, debt, and home loans. The financial decision that they make today could have a high effect towards the long term economic and social aspects (Montoya and Scott, 2011). Personality traits have been found to be a factor that affect an individual’s subjective well-being. This study intends to fill such gap in the literature and provides academics and practitioners with a new understanding of how personality traits influence one’s ability to digest and implement the financial information provided to them. This research purpose is to identify the relationship between personality and financial literacy using the Big Five personality traits and Locus of Control. Data for this research was gathered using online questionnaires and analyzed using Ordinary Least Square. Data analysis shows that from seven personality factors, only Openness and Conscientiousness that not have a significant relationship towards financial literacy.Keywords: Personality Traits, Financial Literacy, Generation Z